Systematic review of barriers to, and facilitators of, the provision of high‐quality midwifery services in India. Issue 4 (25th July 2020) - McFadden, Alison; Gupta, Sunanda; Marshall, Joyce L.; Shinwell, Shona; Sharma, Bharati; McConville, Fran; MacGillivray, Steve
Abstract: Background: The Indian government has committed to implementing high‐quality midwifery care to achieve universal health coverage and reduce the burden of maternal and perinatal mortality and morbidity. There are multiple challenges, including introducing a new cadre of midwives educated to international standards and integrating midwifery into the health system with a defined scope of practice. The objective of this review was to examine the facilitators and barriers to providing high‐quality midwifery care in India. Methods: We searched 15 databases for studies relevant to the provision of midwifery care in India. The findings were mapped to two global quality frameworks to identify barriers and facilitators to providing high‐quality midwifery care in India. Results: Thirty‐two studies were included. Key barriers were lack of competence of maternity care providers, lack of legislation recognizing midwives as autonomous professionals and limited scope of practice, social and economic barriers to women accessing services, and lack of basic health system infrastructure. Facilitators included providing more hands‐on experience during training, monitoring and supervision of staff, utilizing midwives to their full scope of practice with good referral systems, improving women's experiences of maternity care, and improving health system infrastructure. Conclusions: The findings can be used to inform policy and practice. Overcoming the identified barriers will be critical to achieving the Government of India's plans to reduce maternal and neonatal mortality through the introduction of a new cadre of midwives. This is unlikely to be effective until the facilitators described are in place.